Respuesta :
Answer:
[tex](x + 3)^{2} + (y - 10)^{2} = 10^{2}[/tex].
Step-by-step explanation:
There are three quantities in the equation of a circle in a plane:
- [tex]x[/tex]-coordinate of the center of the circle,
- [tex]y[/tex]-coordinate of the center of the circle, and
- radius of the circle.
Let [tex](a,\, b)[/tex] denote the center of this circle and let [tex]r[/tex] denote the radius of this circle ([tex]r > 0[/tex].) The equation of this circle would be:
[tex](x - a)^{2} + (y - b)^{2} = r^{2}[/tex].
A point [tex](x_{1},\, y_{1})[/tex] is on this circle if and only if the equation of this circle is satisfied after substituting in [tex]x = x_{1}[/tex] and [tex]y = y_{1}[/tex].
For example, since [tex](-3,\, 0)[/tex] is on this circle, the equation of this circle should continue to hold after substituting in [tex]x = (-3)[/tex] and [tex]y = 0[/tex]:
[tex]((-3) - a)^{2} + (0 - b)^{2} = r^{2}[/tex].
Likewise, for the other two given points that are on this circle, the following would be equations:
[tex](3 - a)^{2} + (2 - b)^{2} = r^{2}[/tex], and
[tex](5 - a)^{2} + (4 - b)^{2} = r^{2}[/tex].
Expand each of these equations using the binomial theorem.
[tex]9 + 6\, a + a^{2} + b^{2} = r^{2}[/tex] (note that [tex]((-3) - a)^{2}[/tex] is equivalent to [tex](3 + a)^{2}[/tex].)
[tex]9 - 6\, a + a^{2} + 4 - 4\, b + b^{2} = r^{2}[/tex].
[tex]25 - 10\, a + a^{2} + 16 - 8\, b + b^{2} = r^{2}[/tex].
These three equations are part of a system of three equations and three unknowns ([tex]a[/tex], [tex]b[/tex], and [tex]r[/tex] with [tex]r > 0[/tex].)
Subtract the second equation from the first to eliminate the non-linear terms ([tex]a^{2}[/tex], [tex]b^{2}[/tex], and [tex]r^{2}[/tex]) and simplify to obtain a linear equation about [tex]a[/tex] and [tex]b[/tex]:
[tex]3\, a + b = 1[/tex].
Likewise, subtract the third equation from the first and simplify to obtain:
[tex]2\, a + b = 4[/tex].
Solve the system of these two equations for [tex]a[/tex] and [tex]b[/tex]:
[tex]a = -3[/tex].
[tex]b = 10[/tex].
Substitute [tex]a = -3[/tex] and [tex]b = 10[/tex] into any one of the three original equations that include [tex]r[/tex] and solve for [tex]r\![/tex]. For example, substituting into the first equation to obtain:
[tex]\begin{aligned}r^{2} &= 9 + 6 \times (-3) + (-3)^{2} + 10^{2} \\ &= 10^{2}\end{aligned}[/tex].
Since [tex]r > 0[/tex], [tex]r = 10[/tex] would be the only solution to this system of equations.
Therefore, the equation of this circle would be [tex](x - (-3))^{2} + (y - 10)^{2} = 10^{2}[/tex].
Simplify to obtain: [tex](x + 3)^{2} + (y - 10)^{2} = 10^{2}[/tex].